A Reverse-Design Strategy for the Track Error of the Qi Tai Telescope Based on Pointing Accuracy. (June 2022) - Li, Na; Duan, Baoyan; Li, Xiangyang; Zheng, Bin; Wu, Jiang
Graphical abstract: Qi Tai Telescope (QTT) with a 110 m caliber, it will become the largest scale steerable telescope in the world. Its repeated pointing accuracy error should be less than 2.5 arc seconds and the telescope structure must satisfy an ultra-high precision requirements. To reduce the difficulty of telescope's design and manufacture, a reverse design method of the track surface was proposed. Firstly, the distribution characteristics of the test data of track error were verified using the skewness coefficient and kurtosis coefficient methods. According to the distribution characteristics, the azimuth track error was simulated by a two scales model. The error of long-period-short-amplitude was defined as the large scale, which was described by the trigonometric function. The short-period-high-amplitude error was recognized as the small scale, and simulated by the fractal function. Based on the two scales model, effect of it on the pointing accuracy was deduced. And then the relationship between the RMS (Root Mean Square) of track error and the RMS value of the telescope's pointing accuracy errors was deduced. Finally, the allowable RMS value of track error was derived from the allowable pointing accuracy errors. To validate the effectiveness of the new design method, two typical radio telescopes (the Green Bank Telescope and the Large Millimeter Telescope) were selected as experimental examples. Through comparison, the theoretical calculated values of the telescope's pointing accuracy are in good agreement with the measured values, with a maximum error less than 10%. Highlights: Reverse design of the track error.** Qi Tai Telescope (QTT) Large radio telescope. Two scales model of the track error. Based on the pointing accuracy. Difficulty of telescope's design and manufacture. Abstract: The Qi Tai Telescope (QTT), which has a 110 m aperture, is planned to be the largest scale steerable telescope in the world. Ideally, the telescope's repeated pointing accuracy error should be less than 2.5 arc seconds (arcsec); thus, the telescope structure must satisfy ultra-high precision requirements. In this pursuit, the present research envisages a reverse-design method for the track surface to reduce the difficulty of the telescope's design and manufacture. First, the distribution characteristics of the test data for the track error were verified using the skewness coefficient and kurtosis coefficient methods. According to the distribution characteristics, the azimuth track error was simulated by a two-scale model. The error of the long period and short amplitude was characterized as large-scale and described by a trigonometric function, while the short period and high amplitude error was characterized as small-scale and simulated by a fractal function. Based on the two-scale model, effect of the error on the pointing accuracy was deduced. Subsequently, the relationship between the root mean square (RMS) of the track error and the RMS of the pointing accuracy error of the telescope was deduced. Finally, the allowable RMS value of the track error was derived from the allowable pointing accuracy errors. To validate the effectiveness of the new design method, two typical radio telescopes (the Green Bank Telescope (GBT) and the Large Millimeter Telescope (LMT)) were selected as experimental examples. Through comparison, the theoretical calculated values of the pointing accuracy of the telescope were consistent with the measured values, with a maximum error of less than 10%.